2004
DOI: 10.1584/jpestics.29.205
|View full text |Cite
|
Sign up to set email alerts
|

5-Aryl-1,3,4-oxadiazole-2-thiols as a New Series of trans-Cinnamate 4-Hydroxylase Inhibitors

Abstract: A series of 5-aryl-1,3,4-oxadiazole-2-thiols was found to inhibit trans-cinnamate 4-hydroxylase (C4H) from Populus kitakamiensis, which was expressed in yeast. 5-Phenyl-1,3,4-oxadiazole-2-thiol showed inhibitory activity comparable to 2-hydroxy-1-naphthoic acid, a known C4H inhibitor. Studies on the structure-activity relationship indicated that the presence of a thiol group was significant for stronger activity. Of the compounds tested, 5-(3-fluorophenyl)-1,3,4-oxadiazole-2-thiol was the most active. AE Pesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Then, the ring closer reaction of compound (2) with carbon disulfide under basic conditions and subsequent acidification yielded the intermediate (3). Subsequent S-substitution on the 1,3,4-oxadiazole ring gave the final products (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Chemical structures of the compounds synthesized were confirmed by 1 H-NMR spectra, IR and elemental analysis data, which are shown below.…”
Section: Instrumental Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…Then, the ring closer reaction of compound (2) with carbon disulfide under basic conditions and subsequent acidification yielded the intermediate (3). Subsequent S-substitution on the 1,3,4-oxadiazole ring gave the final products (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Chemical structures of the compounds synthesized were confirmed by 1 H-NMR spectra, IR and elemental analysis data, which are shown below.…”
Section: Instrumental Analysismentioning
confidence: 86%
“…The ring closure reaction of 2 with carbon disulfide under basic conditions and subsequent acidification yielded intermediate 3. Various reagents, such as alkyl bromide or acyl halide, were then reacted with compound 3 in the presence of potassium hydroxide in order to introduce a substituent onto the sulfur atom at the 5-position of the 1,3,4-oxadiazole ring, so that novel 13 kinds of compounds (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) were provided in moderate to high yield ( Table 1). The results of spectroscopic data, 1 H NMR and 13 C NMR, IR spectra and elemental analysis are presented in the experimental section.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Therefore, identification of novel potent, less toxic and selective mechanism of action anticancer agents remains one of the most imperative health problems. 3 1,3,4-Oxadiazoles are an important class of heterocyclic compounds 4 with a broad range of biological activities such as anti-inflamma- 23-11-2016 tory, analgesic and ulcerogenicity, 5 apoptosisinducer, 6 antimycobacterial, 7 antifungal, 8 antitumor, 3,6,9 P-Glycoprotein Inhibitors, 10 pesticides and insecticides, 11 4-Hydroxylase Inhibitors, 12 anticonvulsant activity 13 etc.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that a series of 5-aryl-1,3,4-oxadiazole-2-thiols inhibited C4H from Populus kitakamiensis, which was expressed in yeast. 3) We further examined several heterocycles, and found that 4-amino-5-phenyl-2,4-dihydro-3H-1,2,4-triazole-3-thione (1) showed strong inhibitory activity against C4H expressed in yeast. Although some 5-aryl-2,4-dialkyl-2,4-dihydro-3H-1,2,4-triazole-3-thiones have been reported to show antidepressant activity, 4) there has been no report on the inhibitory activity of 1 toward C4H.…”
Section: Introductionmentioning
confidence: 99%